The presence of chiricans in the South Pacific of Costa Rica: contributions from historical geography. - Morera-Beita, Carlos (2017)
This article analyzes the presence of chiricanos in Southern Costa Rica. All this is based on secondary references and focused on rebuilding their occupation routes and some geographical factors. In the foundations of these border regions of Costa Rica and Panamá there is a cross-border people that, during the colonial and independent times, was fragmented, but even in this century, they still resist. This is the case of the Ngäbe Bugle.  Due to the wars that took place in the territory currently occupied by Panama, Chiricanos -as people from the Chiriquí province are called, came to look for refuge, grasslands, agricultural lands to finally work at banana plantations. They are the same social network of the mestizo peasantry that dominated the coastal regions of the country –both in the Caribbean and in the Pacific, which facilitated their fusion with other local groups. This article shows that the concept of border responds to political rather than to cultural reasons, because the territory is a continuum, especially in border areas.